Detection of viral antigen and inflammatory mediators in fatal pediatric dengue: a study on lung immunopathogenesis - Moragas, Leandro Junqueira; Arruda, Laíza Vianna; Oliveira, Lucca de Lima Siqueira; Alves, Felipe de Andrade Vieira; Salomão, Natália Gedeão; da Silva, Jemima Fuentes Ribeiro; Basílio-de-Oliveira, Carlos Alberto; Basílio-de-Oliveira, Rodrigo Panno; Mohana-Borges, Ronaldo; Azevedo, Caio Gonçalves; Oliveira, Gabriela Xavier de; Carvalho, Jorge José de; et al. (Frontiers in Immunology, 2025)
IntroductionThe dengue virus (DENV) is the etiological agent that causes dengue fever illness, an arbovirus with a major endemic potential that has become increasingly prevalent in Brazil and has already been associated with fatal cases in children. DENV has tropism for several organs, including lungs causing pulmonary complications. The aim of this article was to evaluate the inflammatory and histopathological profile of the lung tissue of three fatal cases of children infected with DENV, which represents a group more susceptible to fatality due to its incomplete development.MethodsHistopathological analysis was carried out using Hematoxylin and Eosin staining and special stains. While the characterization of the inflammatory response and cellular expression was done by marking the viral protein, macrophages, lymphocytes and pro-inflammatory cytokines.Results and discussionThe results confirm that vascular dysfunctions such as hemorrhage, vascular congestion and edema associated with a mononuclear infiltrate were observed in all three cases. In addition, the presence of viral replication and increased expression of inflammatory markers were also observed. Such findings contribute to the study and description of dengue, especially its effects on lung tissue.